2014
DOI: 10.1155/2014/214353
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining for Identifying Novel Associations and Temporal Relationships with Charcot Foot

Abstract: Introduction. Charcot foot is a rare and devastating complication of diabetes. While some risk factors are known, debate continues regarding etiology. Elucidating other associated disorders and their temporal occurrence could lead to a better understanding of its pathogenesis. We applied a large data mining approach to Charcot foot for elucidating novel associations. Methods. We conducted an association analysis using ICD-9 diagnosis codes for every patient in our health system (n = 1.6 million with 41.2 milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…A recent study of a large population has also reported some novel statistical associations with conditions not previously linked with the Charcot foot: cardiac dysrhythmia, pulmonary eosinophilia and volume depletion . The significance of these findings will require further study.…”
Section: Potential Predisposing Factors In Diseases Other Than Diabetesmentioning
confidence: 86%
“…A recent study of a large population has also reported some novel statistical associations with conditions not previously linked with the Charcot foot: cardiac dysrhythmia, pulmonary eosinophilia and volume depletion . The significance of these findings will require further study.…”
Section: Potential Predisposing Factors In Diseases Other Than Diabetesmentioning
confidence: 86%
“…Greater individualization of medical care will become possible when traditional sources medical information (the history, physical examination, and laboratory panel) can be augmented by 2 new powerful sources of information. These sources are (1) data mining for multidimensional phenotypic data 6 and (2) improved genomic and omics analyses for structural and functional genotypic data, including pharmacogenomic data. 7 This is now the right time to reclassify the use of genomic information in medicine because of newly available sources of phenotypic and genotypic big data.…”
Section: Big Datamentioning
confidence: 99%
“…By the time of the taxonomy report in 2011 the cost was $21 000. 6 In 2014 Illumina launched its HiSeq X Ten Sequencer, which delivers the first $1000 genome. 11 The greater availability of such genetic information combined with new databases have both led to renewed hopes that specific descriptions of patients at the molecular level and individualized predictions of responses to treatments will soon become powerful tools for precision medicine.…”
Section: Role Of Analyses In Precision Medicinementioning
confidence: 99%
“…Bilateral disability has been observed in numbers ranging from 9 to 39% of patients. When MRI is used as a diagnostic method, the detection rate rises to 75% of documented cases [ 2 , 3 ]. Sohn et al [ 4 ] state that the mortality rate is 28.3% within five years in patients with CN.…”
Section: Introductionmentioning
confidence: 99%